2018
DOI: 10.21037/tp.2018.09.01
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to risk stratification using fetal MRI to predict outcomes in congenital diaphragmatic hernia: the preliminary retrospective single institutional study

Abstract: Background: Congenital diaphragmatic hernia (CDH) is a condition with a wide range of severity.Prenatal diagnosis is essential to optimize postnatal management, especially for severe cases. The lung to head ratio (LHR) and liver herniation estimated by prenatal ultrasound has been used as prenatal predictors in CDH. However, reliability of these factors remains to be proven and prediction of outcome from prenatal imaging is still challenging. We propose our new stratification system using lung to liver signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Lung-to-head ratio evaluates lung volume prenatally in CDH infants, and is used as a prognostic marker for outcome [16]. Magnetic resonance imaging is also used to prenatally evaluate the degree of lung hypoplasia, however, this modality has only recently been taken up at our institution and was therefore not evaluated here [32]. Unfortunately, data for "liver-up", lung-to-head ratio, and other possible risk factors were not registered in a consistent and structured manner throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Lung-to-head ratio evaluates lung volume prenatally in CDH infants, and is used as a prognostic marker for outcome [16]. Magnetic resonance imaging is also used to prenatally evaluate the degree of lung hypoplasia, however, this modality has only recently been taken up at our institution and was therefore not evaluated here [32]. Unfortunately, data for "liver-up", lung-to-head ratio, and other possible risk factors were not registered in a consistent and structured manner throughout the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-five patients were included in this study. The mean gestational week at the fetal MRI was 25.08± 1.1 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Among 25 fetuses, 6 were alive and 19 were dead within 30 days after birth.…”
Section: Resultsmentioning
confidence: 99%
“…We thought that this finding may help to predict the survival along with other specific parameters. Yokoi et al (22) proposed a risk stratification using both the detectable lung parenchyma at the apex and the contralateral LLSIR with a cut-off value of 2 on MRI. They reported that all fetuses with detectable lung parenchyma had survived.…”
Section: Discussionmentioning
confidence: 99%
“…Some MRI predictors, such as observed/expected total fetal lung volume (O/E TFLV) ( 18 ), could accurately measure the volume of lungs. However, most of them focused on the three-dimensional volume, which requires higher measurement techniques and greater time investment, so they were not widely used.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them focused on the three-dimensional volume, which requires higher measurement techniques and greater time investment, so they were not widely used. Some scholars suggested using the lung to liver signal intensity ratio (LLSIR) ( 18 , 19 ) to facilitate measurement. Still, the signal intensity may be affected by amniotic fluid, pulmonary interstitial effusion, etc., decreasing measurement accuracy.…”
Section: Discussionmentioning
confidence: 99%